Subcutaneous immunotherapy for allergic rhinitis: an evidence based review of the recent literature with recommendations. Issue 7 (11th January 2013) - Purkey, Michael T.; Smith, Timothy L.; Ferguson, Berrylin J.; Luong, Amber; Reisacher, William R.; Pillsbury, Harold C.; Toskala, Elina
Abstract : Background: Allergic rhinitis is a common allergic disease with increasing prevalence in Western Societies. Medical therapy is first line treatment, and is aimed at reducing symptoms of immunoglobulin E (IgE)‐mediated inflammation of the nasal passages. In patients with disease refractory to medical therapy, subcutaneous immunotherapy is an option. The aim of this study is to update a recent Cochrane review with available level 1 evidence for seasonal and perennial allergic rhinitis. Methods: A systematic review of the literature was performed from 2006 to 2011 and compared with data from a 2007 Cochrane review on immunotherapy for seasonal allergic rhinitis. We included all studies of level 1 evidence. All forms of single extract immunotherapy were considered. Studies with primary asthma related end‐points were excluded. Primary end‐points were instruments of clinical efficacy (ie, symptom‐medication scores) and adverse events. Results: We retrieved 12 level 1 studies for review. In total, 1512 patients were randomized into treatment groups, alternative study groups (alternative duration of therapy or sublingual immunotherapy [SLIT]), or placebo. Efficacy was evaluated based on reported symptom and/or medication score, validated quality of life instruments, immunological assays, challenge testing, and adverse events. Conclusion: Subcutaneous immunotherapy improves symptom and/or medication scores and validated quality of life measures. In addition, associated changes in surrogate markers of immunologic protection are observed. Subcutaneous immunotherapy is safe when administered to carefully selected patients and in settings capable of responding to systemic reactions. Subcutaneous immunotherapy is recommended for patients with seasonal or perennial allergic rhinitis not responsive to conservative medical therapy, and whose symptoms significantly affect quality of life.